2021
DOI: 10.1111/tmi.13591
|View full text |Cite
|
Sign up to set email alerts
|

Association of low birth weight and polyparasitic infection during pregnancy in Lambaréné, Gabon

Abstract: Objective To report the prevalence of polyparasitism during pregnancy in the Lambaréné region of Gabon and its association with newborn birth weight. Method Pregnant women in their third trimester were recruited in a prospective study between November 2011 and March 2015. Parasite infection status was assessed microscopically in stool, urine and blood samples. Maternal demographic and obstetrical characteristics and newborns anthropometric data were collected. Multivariable logistic regression was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Other studies reported the burden of 51.5% in Ethiopia [ 28 ], 21.2% among refugees in Thailand [ 29 ], 38% in Gabon [ 30 ] and this was higher compared to the present study. Possible reasons for the high rate could be the differences in the method of diagnosis and poor living, environmental conditions and lack of awareness regarding the parasitic infections.…”
Section: Discussioncontrasting
confidence: 82%
“…Other studies reported the burden of 51.5% in Ethiopia [ 28 ], 21.2% among refugees in Thailand [ 29 ], 38% in Gabon [ 30 ] and this was higher compared to the present study. Possible reasons for the high rate could be the differences in the method of diagnosis and poor living, environmental conditions and lack of awareness regarding the parasitic infections.…”
Section: Discussioncontrasting
confidence: 82%
“…A safe environment is one of the basic needs of mothers to grow a healthy baby, as well as good nutrition, rest and adequate antenatal care [ 10 ]. In addition, parasitic infections and maternal exposure to different pesticides during pregnancy have also been linked with a higher risk of low birth weight [ 11 , 12 ]. Several studies have also indicated that low birth weight in most developing countries has resulted from exposure to an unsafe indoor environment, mainly due to household air pollution from cooking fuels and environmental tobacco smoke (ETS) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…34 Evidence from other helminth infections suggest that they are also associated with obstetric complications like stillbirth, abortion, intrauterine growth retardation, and LBW. 35 The underlying mechanisms of these associations is unclear, as so far treatment of helminths during pregnancy has not shown benefits in terms of fetal outcomes. 36 Therefore, it is possible that the associations found are more a reflection of underlying social conditions than a direct effect of helminths.…”
Section: Obstetric Complicationsmentioning
confidence: 99%